¿Cuál es la verdadera metodología de los derechos humanos? (Tema Central) - Vázquez Valencia, Luis Daniel (2025)
Human rights are legal, political, social, economic, and cultural phenomena that are analyzed from various disciplines; therefore, it doesn’t exist a single method for studying them. That’s the reason we can say that there are as many approaches and methods as there are research questions and objectives from each of the different disciplines that study human rights. To show that, in the following pages I develop four methodologies used to analyze human rights-related phenomena: 1. The legal tool known as unpacking rights, that helps to operationalize them; 2. The use of statistical models to understand the causes of human rights violations; 3. Network analysis to understand macrocriminality networks as processes of human rights violations; and 4. Life histories to identify patterns in the construction of the identities of human rights defenders. While methodology is important for building systematic knowledge, the central aspect of any research, especially when it’s about human rights, is the objective and main question, which should aim to achieve the useful effect of rights.